МЕТОДИКА РОЗРАХУНКУ ЕНЕРГОСПОЖИВАННЯ В ІНФОРМАЦІЙНО-КОМУНІКАЦІЙНИХ СИСТЕМАХ - Wenguang, Song; Андрущак , В.С.; Кайдан , М.В.; Бешлей , М.І.; Кочан, О.В.; Jun, Su (Інститут електродинаміки НАН України, Київ, 2020)
The methodology for calculating the complex parameter of energy consumption for info-communication networks is proposed. Unlike the known methodologies, the proposed technique takes into account heterogeneity and multilayered network. It also takes into account the parameter of power consumption during the downtime of network equipment in the process of processing of service data blocks, which is quite an important task to improve the accuracy of energy consumption at the stage of implementing an energy-efficient network. According to this method, the energy consumption can be calculated for any network architecture and configuration, network devices configuration and equipment from different manufacturers. References 24, figures 4.